Efektivitas Metode Pembelajaran Discovery Learning pada Mata Pelajaran Dasar Teknik Ketenagalistrikan - Putri, Anisa; Sukardi, Sukardi (Jurnal Pendidikan Teknik Elektro, 2025)
This study was conducted to determine the effectiveness of the learning method of discovery in the learning outcomes of the basic students' electricity techniques in class X TK 3 SMK Negeri 1 Pariaman in the pretest-posttest design. The participants of this study were students of class X TK 3 at SMK Negeri 1 Pariaman. Student learning outcomes are still low which is caused by learning factors that are still teacher-centered, thus affecting student learning outcomes in the cognitive. Therefore, it is necessary to apply the discovery learning method to find out how effective this learning method is in student learning outcomes. This research uses a type of experimental research with a pre-experimental method with a one-group pretest-posttest design. In this study, the instrument test was carried out to determine the validity, reliability, level of difficulty question, and differentiation of questions. The data analysis technique used is the classic completeness of student lessons and effect analysis. Based on the results of the research and processing that has been done, this shows that the average evaluation of posttest learning outcomes has increased which can be seen in many students who get scores that achieve criteria for the achievement of learning objectives. Analysis of effect sizes in large categories. Therefore, the researcher concluded that the learning method of discovery in the subject in the basic subjects of electrical engineering in SMK Negeri 1 Pariaman had an impact on increasing student learning outcomes.